Temperature induced crossing in the optical bandgap of mono and bilayer MoS2 on SiO2 - Park, Y; Chan, C; Taylor, R; Kim, Y; Kim, N; Jo, Y; Lee, S; Yang, W; Im, H; Lee, G (Nature Publishing Group, 2018)
Photoluminescence measurements in mono- and bilayer-MoS2 on SiO2 were undertaken to determine the thermal effect of the MoS2/SiO2 interface on the optical bandgap. The energy and intensity of the photoluminescence from monolayer MoS2 were lower and weaker than those from bilayer MoS2 at low temperatures, whilst the opposite was true at high temperatures above 200 K. Density functional theory calculations suggest that the observed optical bandgap crossover is caused by a weaker substrate coupling to the bilayer than to the monolayer.